The Effect of Interactive Multimedia on Students' Early Reading Skills: A Lesson from Remote Schools - Pujiariani, Asih; Cathrin, Shely (Journal of Languages and Language Teaching, 2025)
Amidst growing concerns over early literacy challenges in rural Indonesia, this study examines the impact of interactive multimedia on improving early reading skills among first-grade students at Banaran 2 Public Elementary School, in Temanggung Regency. The research adopts a Research and Development approach using the ADDIE model and employs a quasi-experimental time-series design. A purposive sampling method was used to select 21 first-grade students based on their early reading difficulties and access to computer facilities. Data collection methods included expert validation, questionnaires, interviews, observations, and reading tests. Findings indicate that the developed multimedia is highly suitable (91.67%) and practical (94.87%) for early reading instruction. Statistical analysis (p < 0.005) confirms its significant impact on students' reading abilities. These results suggest that interactive multimedia can serve as an effective tool for enhancing early literacy in elementary education, particularly in resource-limited settings. To maximize its potential, future research should explore its long-term effects and adaptation in diverse linguistic and educational contexts, providing valuable insights for curriculum development and technology integration in early childhood education.